Options for urban mining and integration with a potential green circular economy in the Peoples Republic of China. - Joshi, Kaushal ([Manila] Asian Development Bank, 2019)
Rapid urbanization, industrialization, and economic growth in the Peoples Republic of China over the last 40 years have contributed to massive land consumption and extraction of natural resources. The country has been applying urban mining to recover resources in areas of e-waste and the 3R principle of reduce reuse recycle is widely accepted. The brief provides options for policy development to mainstream urban mining and make it a part of a broader concept of a future green circular economy that internalizes environmental and social cost, and considers full life cycles when designing and making products.
Keywords: Urbanization -- China; Industrialization -- Economic aspects -- China; Electronic books